2022
DOI: 10.1080/16549716.2021.2013599
|View full text |Cite
|
Sign up to set email alerts
|

Burden of mortality linked to community-nominated priorities in rural South Africa

Abstract: Background Community knowledge is a critical input for relevant health programmes and strategies. How community perceptions of risk reflect the burden of mortality is poorly understood. Objective To determine the burden of mortality reflecting community-nominated health risk factors in rural South Africa, where a complex health transition is underway. Methods Three discussion groups (total 48 participants) representing a cross-section of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…On water, repeated and prolonged periods without piped water documented, as were unreliable and unavailable infrastructure, inadequate service delivery, unregulated sources, empty reservoirs, and poor supply exacerbated by droughts [ 67 ]. We supplemented community intelligence with statistical data on the extent of the burden and its social and circumstantial drivers [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On water, repeated and prolonged periods without piped water documented, as were unreliable and unavailable infrastructure, inadequate service delivery, unregulated sources, empty reservoirs, and poor supply exacerbated by droughts [ 67 ]. We supplemented community intelligence with statistical data on the extent of the burden and its social and circumstantial drivers [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The elements outlined above—pilot work [ 65 ], Cycle 1 community-based process [ 66 – 68 ], multisectoral engagement [ 69 ], VA [ 70 , 71 ], reflective/adaptive element [ 72 ], Cycle 2 redesign [ 73 , 74 ] and Cycle 3 CHW training [ 75 ]—are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…SA have demonstrated the vulnerability of diseases in their variety, from HIV and TB to noncommunicable diseases such as hypertension, diabetes, cardiovascular disease, high maternal, neonatal, and child morbidity, and high levels of trauma and violence (Govender, et al, 2018;Harrichandparsad & Mahomed, 2021;Mattila, et al, 2022). In KZN alone, it was reported that "94% of people living with HIV know their status, and 85% of those people are on HIV treatment" (Ritshidze, 2021, p. 5).…”
Section: The High Burden Of Diseasementioning
confidence: 99%